Biomass, carbon stock and sequestration in various conditions of mangrove forests in Sungai Apit, Siak, Riau, Indonesia - SITI FATONAH; RASOEL HAMIDY; ARAS MULYADI; EFRIYELDI EFRIYELDI (Society for Indonesian Biodiversity, 2023)
Abstract. Fatonah S, Hamidy R, Mulyadi A, Efriyeldi. 2023. Biomass, carbon stock and sequestration in various conditions of mangrove forests in Sungai Apit, Siak, Riau, Indonesia. Biodiversitas 24: 5837-5846. The value of aboveground carbon is influenced by differences in conditions of the mangrove. Therefore, this study aimed to estimate biomass, as well as carbon stock and sequestration in various mangrove forests within Sungai Apit Siak, including natural, rehabilitated, and degraded forests. The Line Transect Plot method was used for sampling. Aboveground biomass was determined using an allometric equation based on mangrove stem diameter. Stem diameter measurements were taken from mangrove vegetation in three forest conditions across three villages in Sungai Apit, Siak. The findings revealed that natural forests contained higher values of biomass, carbon stock, and sequestration at 256, 128, and 470 tons/ha, respectively, compared to rehabilitated and degraded forests. The variability in these parameters across different mangrove forests was influenced by stands characteristics, specifically basal area and mean tree diameter, which were associated with the age of mangrove vegetation and recovery duration. Notably, Rhizophora mucronata, Sonneratia caseolaris, and Avicennia alba exhibited the highest carbon sequestration. These results highlighted that Sungai Apit mangrove forests store a relatively high carbon stock, emphasizing the importance of implementing proper conservation and management measures to ensure sustainability.